A Methodological Framework for Assessing Social Presence in Music Interactions in Virtual Reality - Van Kerrebroeck, Bavo; Caruso, Giusy; Maes, Pieter-Jan (Frontiers in Psychology, 2021)
Virtual reality (VR) brings radical new possibilities to the empirical study of social music cognition and interaction. In the present article, we consider the role of VR as a research tool, based on its potential to create a sense of ‘social presence’: the illusory feeling of being, and socially interacting, inside a virtual environment. This makes VR promising for bridging ecological validity (“research in the wild”) and experimental control (“research in the lab”) in empirical music research. A critical assumption however is the actual ability of VR to simulate real-life social interactions, either via human-embodied avatars or computer-controlled agents. The mediation of social musical interactions via VR is particularly challenging due to their embodied, complex, and emotionally delicate nature. In this article, we introduce a methodological framework to operationalize social presence by a combination of factors across interrelated layers, relating to the performance output, embodied co-regulation and subjective experiences. This framework provides the basis for the proposal of a pragmatic approach to determine the level of social presence in virtual musical interactions, by comparing the outcomes across the multiple layers with the outcomes of corresponding real-life musical interactions. We applied and tested this pragmatic approach via a case study of piano duet performances of the piece Piano Phase composed by Steve Reich. This case-study indicated that a piano duet performed in VR, in which the real-time interaction between pianists is mediated by embodied avatars, might lead to a strong feeling of social presence, as reflected in the measures of performance output, embodied co-regulation and subjective experience. In contrast, although a piano duet in VR between an actual pianist and a computer-controlled agent led to a relatively successful performance output, it was inadequate in terms of both embodied co-regulation and subjective experience.